Analisis Pengaruh Budaya Organisasi, Gaya Kepemimpinan, dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Pemerintah Kabupaten Deli Serdang - juliadi juliadi; yulita triadiarti; akmal huda nasution (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2016)
The problems discussed in this study is whether the organizational culture, leadership style and job satisfaction simultaneously affect the performance of employees at the Department of Public Works Deli Serdang regency. This study aims to determine the influence of the analysis of organizational culture, leadership style and job satisfaction on employee performance in Deli Serdang regency administration. The population in this study was an employee at the Department of Public Works Deli Serdang regency. Sources of data in this study are derived from primary data in the form of questionnaire respondents. The variable in this study is vaiabel free (independent), ie Cultural Organization (X1), Leadership Style (X2) and Job Satisfaction (X3). While the dependent variable ( devendent ) is Employee Performance (Y). Data analysis used is multiple regression analisia (multiple regretion).The results showed that simultaneous organizational culture has a significant negative effect on the performance of employees at the Department of Public Works Deli Serdang regency, in other words Ha rejected. While the leadership style and job satisfaction have a significant positive effect on the performance of employees at the Department of Public Works Deli Serdang regency , in other words Ha accepted. Significant value of 0.000 and the value of F at 25 056 . Significance value less than 0.05 and the value of F is greater than F table value (25.056 > 2.911). This is evidenced from the influence of organizational culture on employee performance declined significantly, while the leadership style and satisfaction significantly acceptable .The conclusion of this study is organizational culture has a significant negative effect on the performance of employees at the Department of Public Works Deli Serdang, while the leadership style and job satisfaction has a significant positive effect on the performance of employees at the Department of Public Works Deli Serdang regency administration simultaneously